Reliability and accuracy of a radiographic analysis method for posterior maxillary mini-implant location - Luís Carlos Sampaio Dias; Yomara Barreto da Costa Ferreira; Rudys Rodolfo de Jesus Tavarez; Célia Regina Maio Pinzan-Vercelino; Júlio de Araújo Gurgel (University of São Paulo, 2012)
OBJECTIVE: The purpose of this study was to evaluate the reliability and accuracy of a radiographic analysis method for the location of mini-implants inserted in the posterior region of the maxilla. MATERIAL AND METHODS: Two self-drilling mini-implants were installed between the second premolar and the first molar on the right side and left side in three dry skulls. Three operators performed three occlusal radiographs, using an occlusal x-ray film holder, at three different times in each of the three skulls. RESULTS: The interclass correlation coefficient showed a significantly high, positive correlation (p<0.05), indicating an excellent reliability between operators. The analysis of variance showed no significant differences in time and among the operators. CONCLUSION: Based of these findings, it may be concluded that this methodology can be used by several operators in longitudinal clinical studies on orthodontic mini-implants at the anterior-posterior and lateral-medial locations or longitudinal displacement.